Structure, luminescence properties and energy transfer of Tb3+–Eu3+ codoped LiBaB9O15 phosphors. Issue 38 (14th October 2015) - Li, Ting; Li, Panlai; Wang, Zhijun; Xu, Shuchao; Bai, Qiongyu; Yang, Zhiping
<x xml:space="preserve">Abstract</x> A series of single-composition phosphors LiBaB9O15:Tb3+, Eu3+ have been prepared via a high-temperature solid-state reaction process.